The Correlation between Total Ischemic Time with Length of Hospitalization : a Single Centre Report - Eriawan Agung Nugroho; Muhamad Azwin Kamar; Dila Junita (Chemical Engineering Diponegoro University, 2019)
Kidney transplantation is recognized as an advanced modern therapeutic modality for patients with end stage renal failure. Cold Ischemic Time (CIT) has been found as an important independent risk factor for delay graft function (DGF) in kidney transplantation. Recent studies suggested that prolonged Warm Ischemic Time (WIT) may decrease graft’s survival in living kidney transplantation donor.This study aimed to evaluate the total ischemic time during recipient surgery and accessed its contribution for hospitalization time in kidney transplantation patients.This is an observational, cross sectional study. The datawas collected from medical record of patient who underwent kidney transplantation from 2014 until December 2018at Kariadi General Hospital Semarang. There were 28 patients, 18 were maleand 10 were female.Total ischemic time was compared with length of hospitalization. Data was analyzed with Spearman test in SPSS version 23. The study showed that total ischemic time was significantly correlated with hospitalization time (p < 0.001). However, donor’s age did not affect prolonged total ischemic time with p = 0.673, which is not significant (significant if p value < 0.05). In conclusion, total ischemic time has a significant correlation with hospitalization time. In contrary, no significant correlation between donor’s age and prolonged total ischemic time.